2019
DOI: 10.4252/wjsc.v11.i4.222
|View full text |Cite
|
Sign up to set email alerts
|

Application of mesenchymal stem cell therapy for the treatment of osteoarthritis of the knee: A concise review

Abstract: Osteoarthritis (OA) refers to a chronic joint disease characterized by degenerative changes of articular cartilage and secondary bone hyperplasia. Since articular cartilage has a special structure, namely the absence of blood vessels as well as the low conversion rate of chondrocytes in the cartilage matrix, the treatment faces numerous clinical challenges. Traditional OA treatment ( e.g ., arthroscopic debridement, microfracture, autologous or allogeneic cartilage transplantation, chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 80 publications
(60 reference statements)
1
67
0
Order By: Relevance
“…Despite the incredibly small number of MSCs found in BMC; there is extensive literature reporting clinical efficacy in animals and humans using BMC for the treatment of OA. [3][4][5][7][8][9][10][11] This effect cannot be dependent upon BMC/MSC cell survival or differentiation. The efficacious effect must be from the release of acellular paracrine factors.…”
Section: Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the incredibly small number of MSCs found in BMC; there is extensive literature reporting clinical efficacy in animals and humans using BMC for the treatment of OA. [3][4][5][7][8][9][10][11] This effect cannot be dependent upon BMC/MSC cell survival or differentiation. The efficacious effect must be from the release of acellular paracrine factors.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…This acellular biologic treatment can all be achieved with a single arthritic joint injection, not requiring the morbidity and cost of obtaining autogenous MSCs. The future of regenerative medicine in orthopedics and spine may well be the utilization of highly concentrated acellular MSC derived growth factors and especially exosomes [7][8][9][10][11].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…A large number of studies on the biological properties of MSCs have shown their potential for the treatment of OA in humans, by increasing chondrocyte proliferation rates and extracellular matrix production, as well as by their immunomodulatory capacity (Kong et al, 2017). Results from preclinical and clinical studies show that intra-articular injection of MSCs can reduce pain and improve the joint's function, but also suggest that more studies are required for higher levels of evidence (reviewed in Sasaki et al, 2019;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have the capacity to secrete an array of immunosuppressive factors [indoleamine-pyrrole 2,3-dioxygenase(IDO), TNFα-stimulated gene-6(TSG6), nitric oxide (NO), IL-10, galectins, prostaglandin E 2 (PGE2), and transforming growth factor (TGF)-β] to modulate the local inflammatory environment. 22,23 These MSC paracrine mechanisms also maintain the capacity to regulate inflammatory cell action through suppression of T-cells (proliferation and chemotaxis) and of B-cells (differentiation and chemotaxis) to further aid in modulating the inflammatory response. [23][24][25] MSCs often act as sensors of the local environment and their secretome changes in response to local environmental signals; one promising approach for providing a control point for the MSC secretome is through the use of three-dimensional (3D) biomaterial constructs to deliver MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…39 A distinct gap in the pre-clinical literature is that the majority of the work studying MSC efficacy in OA focuses on preventing disease development; however, in clinical scenarios, patients that are treated with cell therapies typically have already developed OA when they seek treatment. 22 There is a fundamental difference in the local environment, and likely the necessary therapeutic mechanism of action, between an injured joint prior to OA development (but primed to develop OA) and a joint where OA is established. Thus, there is a substantial gap in our understanding of the therapeutic efficacy of MSCs in delaying further disease progression once OA is established.…”
Section: Introductionmentioning
confidence: 99%